2009
DOI: 10.1111/j.1460-9568.2009.06973.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct brain networks in recognition memory share a defined region in the precuneus

Abstract: Current models of recognition memory performance postulate that there are two fundamentally distinct retrieval processes, i.e. recollection and familiarity. This view has been challenged and little is known from human research about the functional connectivity of the brain areas involved in these processes. In our study we used a Remember-Know procedure to assess the functional connectivity of brain regions under recognition memory in 30 healthy adults. Using functional magnetic resonance imaging, we analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 84 publications
(252 reference statements)
4
47
0
Order By: Relevance
“…In line with studies of motor imagery (6769), SMA has been found to be functionally connected to precuneus (53, 61, 70, 71), whereas pre-SMA is connected to dorsolateral prefrontal cortex (72). In addition to the well-known executive motor aspects (73), SMA was shown to be involved in sensory and working memory processes in healthy and traumatized participants (74–78) as well as motor inhibition (7982).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In line with studies of motor imagery (6769), SMA has been found to be functionally connected to precuneus (53, 61, 70, 71), whereas pre-SMA is connected to dorsolateral prefrontal cortex (72). In addition to the well-known executive motor aspects (73), SMA was shown to be involved in sensory and working memory processes in healthy and traumatized participants (74–78) as well as motor inhibition (7982).…”
Section: Discussionsupporting
confidence: 69%
“…Underscoring the integrative function of precuneus, connectivity studies revealed this area to be part of a network linking it to cuneus, lingual gyrus, middle frontal gyrus, and supplementary motor area (53, 55, 61) as well as sensorimotor areas and cerebellum in healthy (62) and traumatized samples (4). This network has been shown to be activated specifically during the recollection of autobiographical memory.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were consistent with previous study performed in musicians that long-term motor learning and expertise experience lead to resting-state functional connectivity changes in the default mode network (Fauvel et al, 2014). As precuneus and medial prefrontal cortex highly involve in self-related episodic memory (Dörfel et al, 2009), it may be explained that higher activity in the default mode network is caused by frequently processed self-related episodic memory in basketball playing.…”
Section: Discussionmentioning
confidence: 99%
“…As part of the medial posterior parietal cortex, the precuneus, especially the dorsal subregions of precuneus, has been acknowledged playing a central role in a wide spectrum of highly integrated tasks, including visuo-spatial imagery, episodic memory retrieval (Lundstrom et al, 2003, 2005; Dörfel et al, 2009) and self-processing operations (see Cavanna and Trimble, 2006; Cavanna, 2007 for review). Although the contribution of precuneus to successful encoding has received relatively little attention, it was still found that precuneus is involved in allocentric encoding of spatial locations (Frings et al, 2006).…”
Section: Discussionmentioning
confidence: 99%